Money Isn't Everything - Snyder, Meg,Bragen, Daniel,Rousu, Matthew C.,Snyder, Christopher M. (National Bureau of Economic Research, 2024)
We seek to estimate the prestige value of winning beyond monetary prizes in Cutthroat Kitchen, a cooking show in which dishes are judged in a series of elimination rounds, with the twist that action is periodically paused to auction sabotages against rivals. We estimate the distribution of contestants' prestige values using a structural model of bidding by a contestant with rational expectations about sabotage effectiveness taken from the data. Our most conservative specification–allowing for risk aversion and bias in the beliefs about sabotage effectiveness–yields mean prestige values of nearly 10,000 for typical episodes and over 35,000 for tournaments
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Fernsehprogramm; Auktionstheorie; Auctions; Role and Effects of Psychological; Emotional; Social; and Cognitive Factors on Decision Making; Economics of the Arts and Literature